1998
DOI: 10.1046/j.1365-2168.1998.00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioflavonoid quercetin scavenges superoxide and increases nitric oxide concentration in ischaemia–reperfusion injury: an experimental study

Abstract: Quercetin treatment mollified ischaemia-reperfusion injury to skeletal muscle by scavenging destructive superoxide and enhancing the cytoprotective nitric oxide concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
9

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 22 publications
3
76
0
9
Order By: Relevance
“…Estudos in vitro têm mostrado que a quercetina e outros flavonóides inibem fortemente a produção de Óxido Nítrico e do Fator de Necrose Tumoral pelas células de Kupffer quando estimuladas pela injúria 8 . A quercetina combate com eficiência os ânions superóxido na isquemiareperfusão 9 . Os efeitos da quercetina e de outros flavonóides na doença hepática não estão bem elucidados.…”
Section: Resultsunclassified
“…Estudos in vitro têm mostrado que a quercetina e outros flavonóides inibem fortemente a produção de Óxido Nítrico e do Fator de Necrose Tumoral pelas células de Kupffer quando estimuladas pela injúria 8 . A quercetina combate com eficiência os ânions superóxido na isquemiareperfusão 9 . Os efeitos da quercetina e de outros flavonóides na doença hepática não estão bem elucidados.…”
Section: Resultsunclassified
“…In a previous study, it has been demonstrated that quercetin has protective effects against IR damage by increasing SOD, CAT, GPx activities in heart 82 . Also, in another study, the increase of the SOD activity has been reported after quercetin treatment 86,89 . Protective effect of quercetin on experimental chronic cadmium nephrotoxicity on rats has been evaluated and increase of the SOD activity by the quercetin has been detected 87 .…”
Section: Resultsmentioning
confidence: 99%
“…During the inflammatory process, the proinflammatory mediators, such as NO, COX-2 and proinflammatory cytokines, are rapidly produced in large amount (Posadas et al, 2000). NO is required in immunological defense mechanisms and maintaining the dilation of blood vessels (Huk et al, 1998). Higher concentration of NO can cause oxidative damage, which is involved in various pathological processes (Stichtenoth and Frolich, 1998;Weinberg, 1998;Nagy and Perl, 2006).…”
Section: Discussionmentioning
confidence: 99%